Ética, educação ambiental e agricultura familiar sustentável: reflexões em torno do desenvolvimento rural local a partir do município de Bonito, Pará - Martins Filho, Jose Rodrigues (2015)
This paper aims to highlight the importance of ethics in the environment highlighting the practice of family farming in Bonito, Pará. In order to do justice to this end, we seek to, through a literature search and data collection drawn from Production Caravan of Secretariat Executive of the Agriculture State of Pará - SAGRI/ PA, understanding how it handles this relationship between the practice of environmental education, ethics and family farmers. Thus, looking up through the contributions of authors such as Capra, Hairstyle, Jacobi and Veiga, place sustainable development as practice for a healthy environment, less polluted and no deforestation. During the search it can check that humans and nature need each other to harmonize and build a better future. The work also aims to draw from the biblical view and environmental education principles that signific